Математическое моделирование и анализ аэроупругих явлений в лопаточном венце турбомашин - Гнесин, Виталий Исаевич; Колодяжная, Любовь Владимировна; Жандковски, Ромуальд; Демченко, Алексей Владимирович (НТУ "ХПИ", 2018)
Предложен численный метод решения связанной задачи нестационарной аэродинамики лопаточного венца турбинной ступени в потоке вязкого газа и упругих колебаний лопаток под действием аэродинамических нагрузок с использованием модального подхода. Проведен численный анализ аэроупругого поведения лопаточного венца последней ступени осевой турбомашины с длиной рабочей лопатки 950 мм. Показано, что все формы колебаний лопаток ротора являются устойчивыми с преобладающей частотой близкой к частоте 1-ой собственной формы колебаний. Предложенный метод решения связанной аэроупругой задачи позволяет прогнозировать амплитудно-частотный спектр колебаний лопаток в потоке газа, включая вынужденные колебания и самовозбуждающиеся (флаттер или автоколебания).

There proposed the numerical method of coupled problem solution of unsteady aerodynamic for turbine stage blade row in viscous gas flow and elastic blades oscillations by the action of aerodynamic loads with use of modal approach. 3D viscous gas flow through the blade row axial turbine stage with periodicity on the whole annulus is described by unsteady Navier-Stokes equations in the form of conservation laws, which are integrated with use of the explicit monotonous finite-volume Godunov’s difference scheme and moving hybrid H-O grid. There performed the numerical analysis of aeroelastic behaviour of axial turbomachine last stage blade row with moving blade length of 950 mm. There shown that rotor blades oscillations are stable with dominant mode frequency closed to frequency of the first natural oscillation mode. The proposed method of solution of coupled aeroelastic problem allows to predict the amplitude-frequency spectrum of blades oscillations in gas flow, including forced oscillations and self-excited oscillations (flutter or autooscillations).
The mathematic modeling and analysis of aeroelastic phenomena in turbomashine blade row
Keywords: вязкий поток; автоколебания; связанная задача; численный метод; viscous flow; autooscillations; coupled problem; numerical